Employee engagement : tools for analysis, practice, and competitive advantage - Macey, William H. (Malden, MA : Wiley, 2009)
Providing practical advice, tools, and case examples, this book translates best practices, ideas, and concepts into concrete steps that will change the level of engagement in any organization.
Engaging engagement -- The "feel and look" of employee engagement -- The key to an engaged workforce : an engagement culture -- Phase 1 of creating and executing an engagement campaign : diagnostics and the engagement survey -- Phase 2 of creating and executing an engagement campaign : action planning and intervention.
Includes bibliographical references (pages 175-184) and indexes.
Print version record.
English.
John Wiley and Sons
Keywords: Employee motivation; Employees -- Attitudes; Personnel -- Motivation; Personnel -- Attitudes; Employee motivation; Employees -- Attitudes; dissertations; Academic theses; Academic theses; 2